Qualidade da água em bacia hidrográfica do Nordeste Brasileiro: uma visão ampliada com índice de qualidade da água, índice de poluição e métodos multicritério - Moreira, Yanka Wandréia Nogueira (2024)
This research approaches an evaluation of the surface water quality at nine points in the Salgado basin, Ceará, Northeast Brazil, during the period from 2018 to 2022. From a methodological perspective, it explored different assessment methods through two studies. The first study used the CCME Water Quality Index (CCME WQI) and the Nemerow Pollution Index (NPI), comparatively, considering the annual cycles. The results showed that water quality varied from "Slightly Polluted" to "Heavily Polluted" according to NPI, and from "Good" to "Poor" according to CCME WQI. Moreover, NPI proved to be more restrictive in categorizing quality classes than CCME WQI, leading to the conclusion that CCME WQI seems more appropriate for routine water quality monitoring programs, while the use of NPI is cautiously suggested for in-depth investigations of polluted areas. The second study addressed multicriteria methods, notably the Analytic Hierarchy Process (AHP) in three formats: AHP, Gaussian AHP, and AHP-TOPSIS. Based on criteria representing the characteristics (physical- chemical and microbiological) of water, the multicriteria analysis revealed a ranking of monitoring points, on an annual perspective, according to the degree of water impairment by pollution. The rankings generated demonstrated consistency, even with variations in the criteria weights and their diverse analytical approaches. This consistency was supported by the similarities found in the ranking obtained by the Bascarón type WQI. The results of this study demonstrate the potential of these tools for decision-making related to the restoration and preservation of these resources, by identifying areas with a higher degree of impact on water quality, in a clear, robust, and less subjective way. Both studies indicated the points SA6, Salgadinho river in Crato, and SA5, Salgadinho river in Juazeiro do Norte, as having the most compromised waters throughout the studied period. Finally, the combination of the studies allowed elucidating the application of techniques that support water resource management and obtaining a multifaceted diagnosis of water quality in the studied watershed.